Challenges for Iranian Women in Daily Urban Safety - Hamedanian, Fatemeh; Ghadermazi, Sirwan (Frontiers in Sociology, 2022)
Ensuring the safety of women as a vulnerable group in urban areas is a very important issue and most relevant to issues such as violence, crime, victims, and depression. This paper aims to define safe city criteria based on different dimensions of the experiences of women in Tehran. The conceptual approach of this study is based on empowering women. This study uses a descriptive and qualitative method. The statistical population includes 50 women aged 19 to 55 who have lived in Tehran for the past five years. The results show that safety is different for men than for women. Three key factors for women's safety are cultural, individual, and physical factors. Physical factors include sidewalks, transportation, and recreational facilities for women. Based on the results of the study, a critical security measure for women would be the recognition of their rights and empowerment.